THE EFFECT OF COMBINATION FOSFOMYCIN AND SAMBILOTO (Andrographis paniculata) LEAF EXTRACT ON THE LEUKOCYTES COUNT, NITRITE LEVELS, AND LACTOFERRIN LEVELS IN WISTAR RATS (Rattus norvegicus) URINARY TRACT INFECTION MODEL - Sutriono, Sutriono; Lestari, Endang Sri; Agung Nugroho, Eriawan; Nindita, Yora; Addin, Sofyan Rais (Faculty of Medicine, Diponegoro University, 2024)
Background: Fosfomycin is the first-line of antibiotic for urinary tract infection (UTI). To prevent antibiotic resistance, antibiotics and herbal medicines combination was developed. Studies have shown that Andrographis paniculata has antimicrobial and anti-inflammatory agent.Objective: To investigate the effect of A. paniculata extract for treating UTI in animal modelMethods: Using post test only control group design, thirty females Rattus norvegicus rats were induced by 1 cc transurethral inoculation of E. coli and then randomly grouped into negative control (NC) received no treatment, positive control (PC) that had 54 mg fosfomycin, and treatment groups which were divided into T1 (A. paniculata 100 mg/kgBW), T2 (A. paniculata 200 mg/kgBW), T3 (fosfomycin 54 mg with A. paniculata 100 mg/kgBW), T4 (fosfomycin 54 mg with A. paniculata 200 mg/kgBW). Urinary samples were utilized to count leukocytes under microscope, nitrite levels with a dipstick, and lactoferrin using ELISA.Results: Combination of fosfomycin and A. paniculata led to a reduction in the number of leukocytes and nitrite levels compared to the single therapy group, particularly in T4 group (p<0.001). There were no significant differences in lactoferrin levels among all study groups (p>0.05).Conclusion: Combination of A. paniculata with fosfomycin resulted in a more pronounced reduction in the number of leukocytes and nitrite levels compared to single therapy, while lactoferrin levels were unaffected.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//